The role of predictive and preview effects in Mongolian reading: evidence from eye movements - Lu, Zhang; Ri, Na; Jingxin, Wang (Frontiers in Psychology, 2024)
Introduction The research on contextual predictability in reading has been thoroughly investigated in the context of horizontal text comprehension. However, the performance of contextual predictive effects in Mongolian vertical reading remains unknown. Methods To explore this, we conducted an eye-tracking study using a boundary paradigm. Our study aimed to investigate contextual predictability and preview effects in Mongolian reading. Results We found significant main effects of predictability and previewing on temporal indicators. However, there were no significant effects on skipping rates, and no interaction between predictability and previewing was observed. Discussion We speculate that the unique reading orientation and writing features of Mongolian, compared to horizontally read phonetic scripts, reduce the parafoveal processing of preview information, leading to lower skipping rates in Mongolian reading.